Iterative Finite Element Method Applied to the Nonlinear Electric Field of ±400kV Converter Transformer Barrier System. Issue 1 (May 2021) - Shiling, Zhang; Yongliang, Ji
Abstract: The DC steady-state and the polarity reversal (PR) are typical states of composite insulation in converter transformer barrier system, and the insulation medium has the strong E-field and temperature nonlinear characteristic, so the DC steady-state and polarity reversal E-field will be affected by the variation of electric parameters under temperature gradient. The FEM was applied to the quantitative E-field analysis considering electric and temperature nonlinear factors simultaneously. First, the nonlinear relationship between conductivity with E-field and temperature of medium has been obtained by experiments. Then, the iterative FEM was proposed and verified by coaxial insulation with analytical solution. Finally, the full-scale model of ±400kV converter transformer barrier system has been established, the DC steady-state and polarity reversal E-field has been calculated with the proposed method. The results show that under linear and nonlinear conditions the E-field is quite different, and E-field non-linearity can inhibit the local high electric spot, temperature non-linearity can reduce the E-field in the high temperature area and increase that in the lower temperature area. Under the temperature gradient condition, the local high E-field spot is easy to occur in the PR process. The iterative FEM and calculation results can provide references for the design of converter transformer barrier system.